Dysfunctional beliefs about health and illness: A family study - Arnáez, Sandra; García-Soriano, Gemma; Belloch, Amparo (Anales de Psicología / Annals of Psychology, 2018)
Cognitive models about hypochondriasis postulate that early experiences with illness can lead individuals to develop dysfunctional beliefs about having an illness. These beliefs can remain in a latent state and be triggered by a critical incident. Published studies have provided data partially supporting these assumptions. Considering that the primary family context shares experiences about illness, we examined the relationships between the dysfunctional beliefs that parents and their offsprings maintain about illness and thoughts, such as intolerance to uncertainty and over-estimation of threat, as well as the relationships between these beliefs with hypochondriacal and depressive symptoms. Forty university students and their parents (27 fathers and 36 mothers) completed self-reports on dysfunctional beliefs about illness, thoughts and symptoms of hypochondriasis and depression. Results indicated that the fathers’ dysfunctional beliefs about illness and overestimation of threat, but not those of mothers, were associated with their sons and daughters beliefs. Likewise, the dysfunctional beliefs of fathers, sons, and daughters were related to symptoms of hypochondriasis and depression.